1998
DOI: 10.1191/026921598672167702
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of depression in aphasic stroke patients: the development of the Stroke Aphasic Depression Questionnaire

Abstract: The SADQ may be used for assessing depressed mood in aphasic patients in the community though further validation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 23 publications
0
137
0
3
Order By: Relevance
“…A key difference between the PHQ-9 and other depression scales is that it is based on the 9 DSM-IV symptoms of depression, which facilitates its use as a depression diagnostic tool as well as a screening instrument. Further, although other scales may perform differently in different ethnic groups or among patients of different age or gender, 23,24 this critical aspect of scale measurement is infrequently assessed. We found that the PHQ-9 performed equally well regardless of age, gender, or ethnicity, suggesting that it can be confidently used even in a heterogeneous group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A key difference between the PHQ-9 and other depression scales is that it is based on the 9 DSM-IV symptoms of depression, which facilitates its use as a depression diagnostic tool as well as a screening instrument. Further, although other scales may perform differently in different ethnic groups or among patients of different age or gender, 23,24 this critical aspect of scale measurement is infrequently assessed. We found that the PHQ-9 performed equally well regardless of age, gender, or ethnicity, suggesting that it can be confidently used even in a heterogeneous group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…), though it does not imply a diagnosis of the condition, similar to alternative depression rating scales. 28 The WDI has previously been used with success in studies investigating depression in patients with other pathologies 29,30 and, furthermore, can independently be completed by the patient, reducing investigator bias.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A score Ն14 out of a possible 30 was considered a positive sign of depression. The Stroke Aphasic Depression Questionnaire has been validated against Hospital Anxiety and Depression Scale in community patients with stroke 17 and in a care home setting. 12 Each complication was considered as a single dichotomous (present/absent) variable.…”
Section: Depressionmentioning
confidence: 99%